Sodium-rich P2 / O3 dual-phase layered oxide and preparation method thereof, sodium ion battery positive electrode material and battery

By using sodium-rich P2/O3 biphase layered oxide as the positive electrode material in sodium-ion batteries, the problem of irreversible loss of sodium-ion batteries during the first charging and embedding process is solved, and the energy density and production of sodium-ion batteries are improved and the energy density of sodium-ion batteries are improved. Simplified process.

CN116573683BActive Publication Date: 2024-12-27BEIHANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310370919.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-07
Publication Date
2024-12-27
Estimated Expiration
2043-04-07

AI Technical Summary

Technical Problem

During the first charging and sodium-immobilization process, the formation of SEI film and side reactions of sodium ions lead to severe irreversible loss of sodium ions, which limits the energy density of the battery and the application of materials.

Method used

Sodium-rich P2/O3 biphase layered oxide is used as the cathode material for sodium ion batteries. The excess sodium content makes up for irreversible sodium loss, avoiding the cumbersome production process and sodium supplementation agents. Yamato side reaction problem.

Benefits of technology

It realizes effective sodium supplementation during the first charging and discharging process, improves the energy density and cycle stability of sodium ion batteries, simplifies the production process, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116573683B_ABST
    Figure CN116573683B_ABST
Patent Text Reader

Abstract

The invention discloses a sodium-rich P2 / O3 two-phase layered oxide and a preparation method thereof, a sodium ion battery positive electrode material and a battery, wherein the chemical formula of the sodium-rich P2 / O3 two-phase layered oxide is Na x A y M z O2, wherein Na represents sodium, A is selected from nickel and manganese; M represents a doping element, and M is selected from at least one metal element other than sodium, nickel and manganese in the third to fifth periods of the periodic table, x>1, 0.8≤y<1, 0<z≤0.2, y+z=1. Aiming at the technical problem of serious irreversible loss in sodium ion batteries, the present invention provides another technical route different from the prior art through pre-sodiumization or addition of sodium supplement, that is, using sodium-rich P2 / O3 dual-phase layered oxide as the positive electrode material of sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion batteries, and in particular relates to a sodium-rich P2 / O3 layered oxide and a preparation method thereof, a sodium ion battery positive electrode material and a battery. Background Art

[0002] In recent years, sodium-ion batteries have developed rapidly. With their low cost and high safety, they are expected to become a substitute for lithium-ion batteries in many fields. In order to meet the needs of practical applications, sodium-ion batteries require electrode materials to have higher specific capacity to achieve higher energy density. At present, hard carbon has become one of the most likely negative electrode materials for sodium-ion batteries for industrial application due to its high capacity and high stability. However, due to the fact that the hard carbon negative electrode has more defects and a larger specific surface area, the first sodium insertion process is accompanied by the formation of SEI film and more side reactions, resulting in serious irreversible loss of sodium ions. For the sodium-ion full battery system, all sodium ions used for deintercalation come from the positive electrode material. Any irreversible loss of sodium ions will lead to a decrease in the energy density of the whole battery, making it difficult for many promising sodium-deficient positive electrode materials (such as P2 phase and P2 / O3 dual-phase layered oxide positive electrode materials) to be applied.

[0003] Zhao et al. (Science 2020, 370, 708-711) accurately distinguished the structural competition relationship between the P2 phase and the O3 phase by introducing the cationic potential. According to the theory proposed by them, as the Na content increases, the average Na ion potential increases, and the electrostatic repulsion shielding between the TMO2 plates increases, which is conducive to the formation of the O3 phase structure. They used the cationic potential to achieve charge compensation by reducing the Li content and increasing the Mn content, and designed a P2 phase high sodium content positive electrode material Na 5 / 6 Li 5 / 18 Mn 13 / 18 O2, which is also the P2-phase layered oxide positive electrode material with the highest Na content reported so far. According to this theory, the Na content in the P2-phase layered oxide is difficult to exceed its reported theoretical value (Na=5 / 6).

[0004] At present, researchers mainly solve the irreversible sodium loss during the first sodium insertion process by adding sodium supplements or pre-sodiumizing the negative electrode materials. For example, Cui et al. (ACSnano2011,5(8),6487-6493.) first assembled the negative electrode materials into a half-cell and then charged and discharged them to form a SEI film on the surface of the negative electrode. Then, they disassembled the battery and took out the negative electrode materials to assemble a full battery. Although this method can achieve sodium supplementation at the negative electrode, the process is cumbersome and not suitable for industrial production; Zhang et al. (Energy&Environmental Science2016,9(10),2978-3006) used Na3P as a sodium supplement to compensate for the irreversible sodium loss, and the energy density of the assembled full battery was significantly improved. However, Na3P has poor air stability, and its decomposition products may react with the positive electrode material or electrolyte, resulting in reduced battery stability;

[0005] Although pre-sodiumization or addition of sodium supplements can compensate for irreversible sodium loss to a certain extent, the pre-sodiumization process is relatively complicated, and some sodium supplements have poor air stability and may produce harmful products when decomposed, which makes the above scheme unsuitable for industrial production. Therefore, it is necessary to develop a new type of sodium-rich layered oxide positive electrode material to avoid pre-sodiumization of negative electrode materials or addition of sodium supplements in the production process of sodium-ion batteries. Summary of the invention

[0006] The present invention aims at the technical problem that during the first charge and sodium insertion process of sodium ion batteries, the formation of SEI film and more side reactions lead to serious irreversible loss of sodium ions, and provides a sodium ion positive electrode material, that is, a sodium-rich P2 / O3 two-phase layered oxide. In other words, in order to solve the technical problem that sodium ion batteries have serious irreversible loss, another technical route different from the prior art through pre-sodiumization or adding sodium supplement is provided, that is, using sodium-rich P2 / O3 two-phase layered oxide as the positive electrode material of sodium ion batteries.

[0007] The first aspect of the present invention provides a sodium-rich P2 / O3 dual-phase layered oxide, the chemical formula of which is Na x A y M z O2, wherein Na represents sodium element, A is selected from nickel (Ni) and manganese (Mn) elements; M represents a doping element, and M is selected from at least one metal element other than sodium, nickel and manganese in the third to fifth periods of the periodic table, x>1, 0.8≤y<1, 0<z≤0.2, y+z=1.

[0008] In some embodiments, M is selected from iron (Fe), cobalt (Co), copper (Cu), titanium (Ti), magnesium (Mg), zinc (Zn), calcium (Ca), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tin (Sn), antimony (Sb), and aluminum (Al).

[0009] In some embodiments, the chemical formula of the sodium-rich P2 / O3 dual-phase layered oxide is Na x Ni α Mn β M z O2, y=α+β, 0<α≤0.4, 0<β≤0.7; preferably, 0.1≤α≤0.4, 0.1≤β≤0.7; more preferably, 0.2≤α≤0.33, 0.6≤β≤0.7; even more preferably, 0.23≤α≤0.33, 0.67≤β≤0.7.

[0010] In some embodiments, the XRD diffraction pattern of the sodium-rich P2 / O3 dual-phase layered oxide includes: diffraction peaks (or characteristic peaks) of the P2 phase crystal planes (002), (004), (100), (102), (103), and (104); and diffraction peaks of the O3 phase crystal planes (003), (006), (101), (102), and (104).

[0011] In some embodiments, 1<x≤1.5; preferably 1.1≤x≤1.34.

[0012] In some embodiments, the M is selected from five or more metal elements in the third period to the fifth period of the periodic table (high entropy doping).

[0013] In some embodiments, the chemical formula of the sodium-rich P2 / O3 dual-phase layered oxide is Na x (Ni α Mn β )(M 1a M 2b M 3c M 4d M 5e M 6f )O2, y=α+β, z=a+b+c+d+e+f, M1, M2, M3, M4, M5, M6 represent different doping elements, 0.1≤α≤0.4, 0.1≤β≤0.7, 0<a≤0.05, 0<b≤0.05, 0<c≤0.05, 0<d≤0.05, 0<e≤0.05, 0≤f≤0.05.

[0014] In some embodiments, 0<a≤0.04, 0<b≤0.04, 0<c≤0.04, 0<d≤0.04, 0<e≤0.04, 0≤f≤0.04; more preferably, 0<a≤0.03, 0<b≤0.03, 0<c≤0.03, 0<d≤0.03, 0<e≤0.03, 0≤f≤0.03. In a preferred embodiment, 0<a≤0.02, 0<b≤0.02, 0<c≤0.02, 0<d≤0.02, 0<e≤0.02, 0≤f≤0.02. In another preferred embodiment, at least 4 values ​​of a to f are ≤0.02 and greater than 0. The content of doping elements is also one of the factors that affect its performance as a positive electrode material for sodium ion batteries, and the higher the doping content is not necessarily better. On the contrary, a lower doping amount is beneficial to improving the electrochemical performance of high-entropy doped layered oxides as positive electrode materials for sodium ion batteries.

[0015] In some embodiments, the doping elements include at least 1 to 3 metal elements selected from the fifth period and at least 2 to 4 metal elements selected from the third period and / or the fourth period.

[0016] In some embodiments, the metal elements of the fifth period are selected from zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tin (Sn), and antimony (Sb); the metal elements of the third period are selected from magnesium (Mg) and aluminum (Al); the metal elements of the fourth period are selected from calcium (Ca), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), cobalt (Co), copper (Cu), and zinc (Zn).

[0017] The second aspect of the present invention provides a method for preparing the above-mentioned sodium-rich P2 / O3 dual-phase layered oxide, the steps comprising:

[0018] According to the stoichiometric molar ratio of sodium, nickel, manganese and doping element being x:α:β:z, sodium salt, nickel oxide, manganese oxide and oxide of doping metal element in corresponding molar ratios are weighed and mixed to obtain mixed powder; preferably, the sodium salt is selected from at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate, sodium nitrate and sodium hydroxide;

[0019] Pressing the mixed powder after mixing to obtain a pressed block;

[0020] The block is sintered.

[0021] In some embodiments, the mixing process is performed by ball milling; preferably, in the ball milling, the ball-to-material mass ratio is (5-20):1, and the ball milling time is 3 to 24 hours.

[0022] In some embodiments, in the above-mentioned pressing step, the step more specifically includes loading the mixed powder into a mold and pressing and molding it under pressure; preferably, the pressing pressure is 5 to 30 MPa.

[0023] In some embodiments, in the above sintering step, the sintering temperature is between 500 and 1100°C, and the sintering time is 1 to 24 hours; preferably, the sintering temperature is between 800 and 1000°C; more preferably, between 900°C and 1000°C; more preferably, between 900°C and 980°C; more preferably, between 900°C and 950°C.

[0024] The fourth aspect of the present invention provides a method for preparing a sodium-rich P2 / O3 two-phase layered oxide, comprising the following steps: according to the stoichiometric molar ratio of sodium, nickel, manganese and doping element being x:α:β:z, weighing sodium salt, nickel oxide, manganese oxide and oxide of the doping element in corresponding molar ratios, and mixing them to obtain a mixed powder, wherein x>1, 0<α≤0.4, 0<β≤0.7, α+β+z=1, 0<z≤0.2; the sodium salt is selected from at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate, sodium nitrate and sodium hydroxide; the doping element is selected from at least one of iron (Fe), cobalt (Co), copper (Cu), titanium (Ti), magnesium (Mg), zinc (Zn), calcium (Ca), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tin (Sn), antimony (Sb) and aluminum (Al);

[0025] Pressing the mixed powder after mixing to obtain a pressed block;

[0026] The block is sintered; preferably, the sintering temperature of the sintering treatment is between 800 and 1000°C; more preferably, between 900°C and 1000°C; more preferably, between 900°C and 980°C; more preferably, between 900°C and 950°C.

[0027] In some embodiments, the doping elements are selected from five or more of iron (Fe), cobalt (Co), copper (Cu), titanium (Ti), magnesium (Mg), zinc (Zn), calcium (Ca), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tin (Sn), antimony (Sb), and aluminum (Al).

[0028] In some embodiments, 1<x≤1.5; preferably, 1.1≤x≤1.34.

[0029] In some embodiments, 0.1≤α≤0.4, 0.1≤β≤0.7; preferably, 0.2≤α≤0.33, 0.6≤β≤0.7; more preferably, 0.23≤α≤0.33, 0.67≤β≤0.7.

[0030] A fifth aspect of the present invention provides a sodium-rich P2 / O3 dual-phase layered oxide, wherein the chemical formula of the sodium-rich P2 / O3 dual-phase layered oxide is Na x A y O2, wherein Na represents sodium element, A is selected from nickel (Ni) and manganese (Mn) elements; x>1, y=1.

[0031] In some embodiments, the chemical formula of the sodium-rich P2 / O3 dual-phase layered oxide is Na x Ni α Mn β O2, y=α+β, 0<α≤0.4, 0<β≤0.7; preferably, 0.1≤α≤0.4, 0.1≤β≤0.7; more preferably, 0.2≤α≤0.33, 0.6≤β≤0.7; even more preferably, 0.23≤α≤0.33, 0.67≤β≤0.7.

[0032] In some embodiments, the XRD diffraction pattern of the sodium-rich P2 / O3 dual-phase layered oxide includes: diffraction peaks of P2 phase crystal planes (002), (004), (100), (102), (103), and (104); and, diffraction peaks of O3 phase crystal planes (003), (006), (101), (102), and (104).

[0033] In some embodiments, 1<x≤1.5; preferably 1.1≤x≤1.34.

[0034] The sixth aspect of the present invention provides a method for preparing the above-mentioned sodium-rich P2 / O3 dual-phase layered oxide, characterized in that the steps include:

[0035] According to the stoichiometric ratio of sodium, nickel and manganese elements being x:α:β, sodium salt, nickel oxide and manganese oxide in corresponding molar ratios are weighed and mixed to obtain a mixed powder; preferably, the sodium salt is selected from at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate, sodium nitrate and sodium hydroxide;

[0036] Pressing the mixed powder after mixing to obtain a pressed block;

[0037] The block is sintered; preferably, the sintering temperature of the sintering treatment is between 800°C and 1000°C; more preferably, between 900°C and 1000°C; more preferably, between 900°C and 980°C; more preferably, between 900°C and 950°C.

[0038] The seventh aspect of the present invention provides a sodium ion battery positive electrode material, comprising the above-mentioned sodium-rich P2 / O3 two-phase layered oxide; or, the sodium-rich P2 / O3 two-phase layered oxide obtained by the above-mentioned preparation method.

[0039] An eighth aspect of the present invention provides a sodium ion battery, comprising the above-mentioned sodium ion battery positive electrode material.

[0040] The ninth aspect of the present invention provides an electrical device, comprising the above-mentioned sodium ion battery. The electrical device can be an electric car, an electric motorcycle, an electric bicycle, an energy storage system, an electric tool, an electronic appliance, etc.

[0041] Compared with the prior art, the present invention provides a new sodium supplementation technology for sodium ion batteries, that is, using a sodium-rich P2 / O3 two-phase layered oxide as a sodium ion battery positive electrode material, which can achieve one-time sodium supplementation by using the excess sodium content in the sodium-rich P2 / O3 two-phase layered oxide to compensate for irreversible sodium loss during the first charge and discharge process. The technical route of the present invention avoids the cumbersome production process of pre-sodiumization, as well as the problems of increased positive electrode internal resistance, increased positive electrode porosity, and side reactions caused by the addition of a sodium supplement.

[0042] The sodium-rich P2 / O3 two-phase layered oxide of the present invention is used as the positive electrode material of the sodium ion battery, and the existing sodium ion battery production equipment is still used without adding additional process steps. It can be quickly introduced into the production process of the sodium ion battery and is easy to realize industrial production and application.

[0043] The technical problem solved by the present invention is that the P2 / O3 dual-phase layered oxide in the prior art is a sodium-deficient positive electrode material, in which the sodium content is low, and there is serious irreversible loss of sodium ions in the battery, resulting in low initial coulombic efficiency and low energy density of the whole battery. The present invention provides a sodium-rich P2 / O3 dual-phase layered oxide (Na x A y O2 or Na x A y M z In O2, x>1). BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The sodium-rich P2 / O3 dual-phase layered oxide Na in Example 2 of the present invention 1.33 Ni 0.26Mn 0.67 Cu 0.07 XRD spectrum of O2.

[0045] Figure 2 The sodium-rich P2 / O3 dual-phase layered oxide Na in Example 2 of the present invention 1.33 Ni 0.26 Mn 0.67 Cu 0.07 SEM photo of O2.

[0046] Figure 3 This is the first charge and discharge curve of the sodium-rich P2 / O3 dual-phase layered oxide as the positive electrode material of a sodium ion battery at a rate of 0.1C in Example 2 of the present invention.

[0047] Figure 4 This is the cycle performance curve of the sodium-rich P2 / O3 dual-phase layered oxide in Example 2 of the present invention as a positive electrode material for a sodium ion battery at a rate of 1C.

[0048] Figure 5 The sodium-rich P2 / O3 dual-phase layered oxide in Example 3 of the present invention

[0049] Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01 )XRD spectrum of O2.

[0050] Figure 6 The sodium-rich P2 / O3 dual-phase layered oxide in Example 3 of the present invention

[0051] Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01 )SEM photograph of O2.

[0052] Figure 7 This is the first charge and discharge curve of the sodium-rich P2 / O3 dual-phase layered oxide as the positive electrode material of a sodium ion battery at a rate of 0.1C in Example 3 of the present invention.

[0053] Figure 8 This is the cycle performance curve of the sodium-rich P2 / O3 dual-phase layered oxide in Example 3 of the present invention as a positive electrode material for a sodium ion battery at a rate of 1C.

[0054] Fig. 9The sodium-rich P2 / O3 dual-phase layered oxide Na in Example 4 of the present invention 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Fe 0.03 Cu 0.02 )XRD spectrum of O2.

[0055] Fig.10 The sodium-rich P2 / O3 dual-phase layered oxide Na in Example 4 of the present invention 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Fe 0.03 Cu 0.02 )SEM photograph of O2.

[0056] Fig.11 This is the first charge and discharge curve of the sodium-rich P2 / O3 dual-phase layered oxide as the positive electrode material of a sodium ion battery at a rate of 0.1C in Example 4 of the present invention.

[0057] Fig.12 The cyclic performance of three sodium-rich P2 / O3 dual-phase layered oxides as positive electrode materials for sodium ion batteries at 1C rate in Example 4 of the present invention is compared.

[0058] Fig.13 The figure is a comparison of the rate performance of three sodium-rich P2 / O3 dual-phase layered oxides used as positive electrode materials for sodium ion batteries in Example 4 of the present invention. DETAILED DESCRIPTION

[0059] The technical solution of the present invention is described below by specific embodiments. It should be understood that one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and does not limit the order of arrangement of each method or limit the scope of implementation of the present invention. The change or adjustment of the relative relationship thereof can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.

[0060] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0061] The preparation method of the sodium ion battery positive electrode sheet recorded in the present invention comprises the following steps: 1) mixing the sodium ion battery positive electrode material (sodium-rich P2 / O3 dual-phase layered oxide in the present invention) with a conductive agent (Super P) and a binder (PVDF) in a mass ratio of 7:2:1 and grinding for 10 minutes, then adding an appropriate amount of N-methylpyrrolidone (NMP) and grinding for another 20 minutes to prepare a mixed slurry; 2) coating the obtained mixed slurry on an aluminum foil disc with a diameter of 12 mm, with a loading amount of 1.5 mg / cm 2 , and then dry the coated electrode sheet in a vacuum oven at 80°C for 12 hours.

[0062] The same method is used to replace the sodium-rich P2 / O3 dual-phase layered oxide with other layered oxides (see the specific examples for specific types) to obtain a comparative positive electrode sheet.

[0063] The assembly method of the sodium ion battery recorded in the present invention comprises the following steps: using a metallic sodium sheet as a negative electrode and the positive electrode sheet prepared as above as a positive electrode, making a CR2032 button battery in an argon glove box, wherein a glass fiber diaphragm is used as a diaphragm, an electrolyte is used as a 1M NaClO4 solution, and the solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1, and contains 2% by volume of fluoroethylene carbonate (FEC).

[0064] The charge and discharge performance test of the sodium ion battery in the present invention is carried out on a Land BT2000 battery test system, the test temperature is room temperature, the test voltage range is 1.5 to 4.3V, and the rate range is 0.1 to 5C.

[0065] Example 1

[0066] This embodiment provides a sodium-rich P2 / O3 two-phase layered oxide and a preparation method thereof, that is, a sodium ion battery positive electrode material and a preparation method thereof. The sodium-rich P2 / O3 two-phase layered oxide is represented by a chemical formula: Na x A y M z O2, wherein A is manganese (Mn) and nickel (Ni), M is a doping element, selected from at least one metal element from the third to fifth periods of the periodic table other than sodium, manganese and nickel, x>1, y+z=1, 0.8≤y<1, 0<z≤0.2; it can also be expressed as Na x Ni α Mn β M z O2, x>1, α+β+z=1, 0<α≤0.4, 0<β≤0.7, 0<z≤0.2.

[0067] In some embodiments, 1<x≤1.5; preferably, 1.1≤x≤1.34, or, 1.1≤x≤1.33, or 1.1≤x≤4 / 3.

[0068] In some embodiments, 0.1≤α≤0.4, 0.1≤β≤0.7; preferably, 0.2≤α≤0.33, 0.6≤β≤0.7; more preferably, 0.23≤α≤0.33, 0.67≤β≤0.7.

[0069] In this embodiment, M is selected from at least one of iron (Fe), cobalt (Co), copper (Cu), titanium (Ti), magnesium (Mg), zinc (Zn), calcium (Ca), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tin (Sn), antimony (Sb), and aluminum (Al).

[0070] This embodiment also provides a preferred sodium-rich P2 / O3 two-phase layered oxide, wherein the above-mentioned doping elements (M) include at least 1 to 3 metal elements selected from the fifth period and at least 2 to 4 metal elements selected from the third period and / or the fourth period; through the staggered matching between the sizes of metal atoms in different periods, an entropy-stable high-entropy doped P2 / O3 two-phase layered oxide is obtained, that is, through the staggered matching between metal atoms in different periods, the structural stability of the high-entropy doped P2 / O3 two-phase layered compound can be increased; in a preferred embodiment, the metal elements of the fifth period are selected from zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tin (Sn), and antimony (Sb); the metal elements of the third period are selected from magnesium (Mg) and aluminum (Al); the metal elements of the fourth period are selected from calcium (Ca), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), cobalt (Co), copper (Cu), and zinc (Zn);

[0071] In a specific embodiment, the above-mentioned doping elements (M) include: at least two of titanium (Ti), vanadium (V), chromium (Cr), copper (Cu), zinc (Zn), and magnesium (Mg); and / or, at least one element of tin (Sn), antimony (Sb), niobium (Nb), molybdenum (Mo), and zirconium (Zr).

[0072] In a specific embodiment, the doping elements (M) include five or more doping elements to form high entropy doping.

[0073] In a specific embodiment, the chemical formula of the sodium-rich P2 / O3 dual-phase layered oxide is represented by Na x (Ni α Mn β )(M 1a M 2b M 3cM 4d M 5e M 6f )O2, y=α+β, z=a+b+c+d+e+f, M1, M2, M3, M4, M5, M6 represent different doping elements, 0.1≤α≤0.4, 0.1≤β≤0.7, 0<a≤0.05, 0<b≤0.05, 0<c≤0.05, 0<d≤0.05, 0<e≤0.05, 0≤f≤0.05.

[0074] In some embodiments, 0<a≤0.04, 0<b≤0.04, 0<c≤0.04, 0<d≤0.04, 0<e≤0.04, 0≤f≤0.04; more preferably, 0<a≤0.03, 0<b≤0.03, 0<c≤0.03, 0<d≤0.03, 0<e≤0.03, 0≤f≤0.03. In a preferred embodiment, 0<a≤0.02, 0<b≤0.02, 0<c≤0.02, 0<d≤0.02, 0<e≤0.02, 0≤f≤0.02. In another preferred embodiment, at least 4 values ​​of a to f are ≤0.02 and greater than 0. The content of doping elements is also one of the factors that affect its performance as a positive electrode material for sodium ion batteries, and the higher the doping content is not necessarily better. On the contrary, a lower doping amount is beneficial to improving the electrochemical performance of high-entropy doped layered oxides as positive electrode materials for sodium ion batteries.

[0075] The preparation method of the sodium-rich P2 / O3 dual-phase layered oxide comprises the following steps:

[0076] S11: according to the stoichiometric molar ratio of sodium, nickel, manganese and doped metal element of x:α:β:z, weigh the corresponding molar ratio of sodium source, nickel oxide, manganese oxide and oxide of doped metal element and mix them to obtain mixed powder; wherein 1<x≤1.5, 0.1≤α≤0.4, 0.1≤β≤0.7, α+β+z=1, 0<z≤0.2;

[0077] S12: pressing the mixed powder after mixing to obtain a pressed block;

[0078] S13: sintering the block.

[0079] The stoichiometric molar ratio of each element in step S11 is equal to the ratio of the subscript values ​​corresponding to each element in the chemical formula.

[0080] Among them, in step S11, the sodium salt is selected from one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium acetate (CH3COONa), sodium oxalate (Na2C2O4), sodium citrate (C6H5Na3O7), sodium nitrate (NaNO3), and sodium hydroxide (NaOH); the raw nickel oxide includes NiO and Ni2O3; the manganese oxide includes: MnO, MnO2, Mn2O3, Mn3O4, Mn2O5, etc.

[0081] The purpose of the mixing process in step S11 is to fully and evenly mix the raw materials. Any method that can achieve the purpose of uniform mixing using different mechanical equipment can be used, such as mechanical stirring and dispersion. In a specific embodiment, the mixing process uses a ball milling mixing method, and more specifically, wet ball milling is preferred. The solvent that can be added when wet ball milling includes but is not limited to ethanol, water, N-methylpyrrolidone (NMP), isopropyl alcohol (IPA) and other liquids. The liquid can be submerged in the ball milling balls, and can also be changed according to different situations. The time for wet ball milling can be selected from 3 to 24 hours, and the ball milling speed is 300 to 600r / min; more preferably, the ball milling time is 5 to 20 hours, and the rotation speed is about 300 to 400r / min.

[0082] In the pressing process in step S12, cold pressing is preferably used, and the pressing pressure is 5 to 30 MPa, preferably, the pressure is 5 to 10 MPa.

[0083] In the sintering treatment in step S13, the sintering temperature is between 800 and 1000°C, the heating rate is between 3 and 20°C / min, and the sintering time is between 1 and 24 hours; more preferably, the sintering temperature is between 900°C and 980°C; more preferably, it is between 900°C and 950°C.

[0084] Example 2

[0085] This embodiment provides a specific sodium-rich P2 / O3 dual-phase layered oxide Na 1.33 Ni 0.26 Mn 0.67 Cu 0.07 O2 (or can be expressed as: Na 4 / 3 Ni 0.26 Mn 2 / 3 Cu 0.07 O2), the preparation method thereof comprises the following steps:

[0086] (1) According to the stoichiometric molar ratio of sodium, nickel, manganese and copper elements of 1.33:0.26:0.67:0.07, weigh the corresponding molar ratio of Na2CO3, nickel oxide, manganese oxide and copper oxide, and mix them to obtain a mixed powder; specifically, in the experiment, weigh Na2CO3, NiO, MnO2 and CuO powders according to the molar ratio of 0.665:0.26:0.67:0.07, respectively, and put them in an agate jar, add agate balls according to the ball-to-material mass ratio of 10:1, then add an appropriate amount of ethanol as a grinding aid, and finally put the ball mill jar on a ball mill for 4 hours. After the ball milling is completed, put the ball mill jar in an 80℃ forced air oven and dry it for 10 hours to obtain a mixed powder.

[0087] (2) The mixed powder is pressed to obtain a pressed block; specifically, the dried mixed powder is placed in a mold and pressed at a pressure of 10 MPa to obtain a round block with a diameter of 14 mm.

[0088] (3) sintering the block; specifically, placing the pressed round block into an alumina crucible, placing the crucible into a muffle furnace, sintering for 12 hours in an air atmosphere at 930° C., and cooling with the furnace, grinding and sieving the sintered block to obtain the target product.

[0089] The obtained target product and the comparative sample were tested by X-ray diffraction (XRD). Figure 1 As shown, it can be seen that the target product has characteristic peaks of the P2 phase at 15.7°, 32.3°, 35.8°, 39.6°, 43.6°, and 48.7°. These characteristic peaks (diffraction peaks) of the P2 phase correspond to the (002), (004), (100), (102), (103), and (104) crystal planes, respectively. Among them, (002) is a strong diffraction peak, and (004), (100), (102), (103), and (104) are relatively weak diffraction peaks. The target product has characteristic peaks of O3 phase at 16.3°, 33.4°, 35.5°, 36.4° and 41.6°, and these characteristic peaks of O3 phase correspond to (003), (006), (101), (102) and (104) crystal planes, respectively. Among them, (003) is a strong diffraction peak, and (104), (006), (101) and (102) are relatively weak diffraction peaks, indicating that the target product contains characteristic peaks of both P2 phase and O3 phase, that is, the target product Na 1.33 Ni 0.26 Mn 0.67 Cu 0.07 O2 is a P2 / O3 dual-phase composite structure and is a pure phase, confirming that the sodium-rich P2 / O3 dual-phase layered oxide Na 1.33 Ni 0.26 Mn0.67 Cu 0.07 O2 was successfully synthesized.

[0090] Figure 2 This is a scanning electron microscope (SEM) photograph of the target product. It can be seen that the target product is a layered block with a particle size ranging from 3 to 10 μm.

[0091] This embodiment also provides a use of the above-mentioned sodium-rich P2 / O3 two-phase layered oxide as a positive electrode material for a sodium ion battery, or a sodium ion battery positive electrode material and a sodium ion battery.

[0092] The sodium-rich P2 / O3 dual-phase layered oxide prepared in this example was assembled into a sodium ion battery and its electrochemical performance was tested. Figure 3 and 4 As shown. Figure 3 It can be seen that the P2 / O3 dual-phase sodium-rich layered oxide Na 1.33 Ni 0.26 Mn 0.67 Cu 0.07 The first cycle charge capacity of O2 positive electrode material at 0.1C is 277 mAhg -1 , the discharge capacity is 149 mAh g -1 , which means that the sodium ions transferred from the positive electrode to the negative electrode during charging are far more than those transferred from the negative electrode to the positive electrode during discharging. The excess sodium ions can be used for the primary sodium replenishment of the negative electrode material. Figure 4 The P2 / O3 dual-phase sodium-rich layered oxide Na 1.33 Ni 0.26 Mn 0.67 Cu 0.07 The cycling performance test of the O2 cathode material at 1C rate shows that the cathode material exhibits excellent cycling stability, and the capacity remains at about 100 mAh g after 100 cycles. -1 .

[0093] Example 3

[0094] This embodiment provides a high entropy doped sodium-rich P2 / O3 dual-phase layered oxide Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01 )O2, the preparation method thereof comprises the following steps:

[0095] (1) According to the stoichiometric molar ratio of sodium, nickel, manganese, zinc, niobium, iron, cobalt and copper elements of 1.2:0.26:0.67:0.02:0.02:0.01:0.01:0.01, weigh Na2CO3, nickel oxide, manganese oxide, zinc oxide, niobium oxide, iron oxide, cobalt oxide and copper oxide in corresponding molar ratios, mix them and obtain mixed powder; specifically, in the experiment, weigh Na2CO3, NiO, MnO2, ZnO, Nb2O5, Fe2O3, CoO and CuO powders in a molar ratio of 0.6:0.26:0.67:0.02:0.01:0.005:0.01:0.01, place them in an agate jar, add agate balls in a ball-to-material mass ratio of 10:1, then add an appropriate amount of ethanol as a grinding aid, and finally place the ball mill jar on a ball mill for 4 hours. After the ball milling is completed, the ball mill is placed in an 80°C forced air oven and dried for 10 hours to obtain a mixed powder.

[0096] (2) The mixed powder is pressed to obtain a pressed block; specifically, the dried mixed powder is placed in a mold and pressed at a pressure of 10 MPa to obtain a round block with a diameter of 14 mm.

[0097] (3) sintering the block; specifically, placing the pressed round block into an alumina crucible, placing the crucible into a muffle furnace, sintering for 12 hours in an air atmosphere at 930° C., and cooling with the furnace, grinding and sieving the sintered block to obtain the target product.

[0098] The obtained target product and the comparative sample were tested by X-ray diffraction (XRD). Figure 5 As shown, it can be seen that the target product has characteristic peaks of P2 phase at 15.6°, 32.4°, 35.7°, 39.5°, 43.5°, and 48.6°, and these P2 phase characteristic peaks correspond to the (002), (004), (100), (102), (103), and (104) crystal planes, respectively. Among them, (002) is a strong diffraction peak, and (004), (100), (102), (103), and (104) are relatively weak diffraction peaks. At the same time, the target product has characteristic peaks at 16.5°, 33.3°, and 48.6°. There are characteristic peaks of O3 phase at 35.5°, 36.6° and 41.6°, which correspond to the (003), (006), (101), (102) and (104) crystal planes, respectively. Among them, (003) is a strong diffraction peak, and (104), (006), (101) and (102) are relatively weak diffraction peaks, indicating that the target product contains characteristic peaks of both P2 and O3 phases, that is, the target product is a P2 / O3 dual-phase pure phase, confirming that the sodium-rich P2 / O3 dual-phase layered oxide Na 1.2 Ni0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01 )O2 was successfully synthesized. Figure 2 The scanning electron microscope (SEM) photo of the target product shows that the target product is a layered block with a particle size ranging from 1 to 10 μm. It should be noted that the meaning of "pure phase" in the present invention may include inevitable impurities.

[0099] This embodiment also provides a use of the above-mentioned sodium-rich P2 / O3 two-phase layered oxide as a positive electrode material for a sodium ion battery, or a sodium ion battery positive electrode material and a sodium ion battery.

[0100] The sodium-rich P2 / O3 dual-phase layered oxide prepared in this example was assembled into a sodium ion battery and its electrochemical performance was tested. Figure 7 and 8 As shown. Figure 7 It can be seen that the P2 / O3 dual-phase sodium-rich layered oxide Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01 ) The first cycle charge capacity of O2 positive electrode material at 0.1C is 270mAhg -1 , the discharge capacity is 157mAhg -1 , which means that the sodium ions transferred from the positive electrode to the negative electrode during charging are far more than those transferred from the negative electrode to the positive electrode during discharging. The excess sodium ions can be used for the primary sodium replenishment of the negative electrode material. Figure 8 P2 / O3 dual-phase sodium-rich layered oxides were given.

[0101] Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01 )O2 positive electrode material cycle performance test at 1C rate, it can be seen that the positive electrode material performs better than the layered oxide in Example 2

[0102] Na 1.33 Ni 0.26 Mn 0.67 Cu 0.07O2 has better cycle stability. After 100 cycles, the capacity has hardly decayed and remains at about 115 mAh g -1 .

[0103] Example 4

[0104] This embodiment provides a high entropy doped sodium-rich P2 / O3 dual-phase layered oxide Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Fe 0.03 Cu 0.02 )O2, the preparation method thereof comprises the following steps:

[0105] (1) According to the stoichiometric molar ratio of sodium, nickel, manganese, zinc, iron and copper elements of 1.2:0.26:0.67:0.02:0.03:0.02, weigh the corresponding molar ratio of Na2CO3, nickel oxide, manganese oxide, zinc oxide, iron oxide and copper oxide, and mix them to obtain a mixed powder; specifically, in the experiment, weigh Na2CO3, NiO, MnO2, ZnO, Fe2O3 and CuO powders according to the molar ratio of 0.6:0.26:0.67:0.02:0.015:0.02, and put them in an agate jar, add agate balls according to the ball-to-material mass ratio of 10:1, then add an appropriate amount of ethanol as a grinding aid, and finally put the ball mill jar on a ball mill for 4 hours. After the ball milling is completed, put the ball mill jar in an 80℃ forced air oven and dry it for 10 hours to obtain a mixed powder.

[0106] (2) The mixed powder is pressed to obtain a pressed block; specifically, the dried mixed powder is placed in a mold and pressed at a pressure of 10 MPa to obtain a round block with a diameter of 14 mm.

[0107] (3) sintering the block; specifically, placing the pressed round block into an alumina crucible, placing the crucible into a muffle furnace, sintering for 12 hours in an air atmosphere at 930° C., and cooling with the furnace, grinding and sieving the sintered block to obtain the target product.

[0108] The obtained target product and the comparative sample were tested by X-ray diffraction (XRD). Figure 1As shown, it can be seen that the target product has characteristic peaks of P2 phase at 15.8°, 32.4°, 35.7°, 39.7°, 43.7°, and 48.6°, and these P2 phase characteristic peaks correspond to the (002), (004), (100), (102), (103), and (104) crystal planes, respectively. Among them, (002) is a strong diffraction peak, and (004), (100), (102), (103), and (104) are relatively weak diffraction peaks. At the same time, the target product has characteristic peaks at 16.4°, 33.3°, and 48.6°. At 35.5°, 36.3°, and 41.5°, there are characteristic peaks of O3 phase, which correspond to (003), (006), (101), (102), and (104) crystal planes, respectively. Among them, (003) and (104) are strong diffraction peaks, while (006), (101), and (102) are relatively weak diffraction peaks, indicating that the target product contains characteristic peaks of both P2 and O3 phases, that is, the target product is P2 / O3 dual-phase and pure phase, confirming that the sodium-rich P2 / O3 dual-phase layered oxide Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Fe 0.03 Cu 0.02 )O2 was successfully synthesized. Figure 2 This is a scanning electron microscope (SEM) photograph of the target product. It can be seen that the target product is a layered block with a particle size ranging from 3 to 10 μm.

[0109] This embodiment also provides a use of the above-mentioned sodium-rich P2 / O3 two-phase layered oxide as a positive electrode material for a sodium ion battery, or a sodium ion battery positive electrode material and a sodium ion battery.

[0110] The sodium-rich P2 / O3 dual-phase layered oxide prepared in this example was assembled into a sodium ion battery and its electrochemical performance was tested. Fig.11 It can be seen that the sodium-rich P2 / O3 two-phase layered oxide Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Fe 0.03 Cu 0.02 ) The first cycle charge capacity of O2 positive electrode material at 0.1C is 298 mAh g -1 , the discharge capacity is 148 mAh g -1 , which means that the sodium ions transferred from the positive electrode to the negative electrode during charging are far more than those transferred from the negative electrode to the positive electrode during discharging. The excess sodium ions can be used for the primary sodium replenishment of the negative electrode material.

[0111] Fig.12The cycling performance test results of three sodium-rich P2 / O3 dual-phase layered oxides with different doping elements at 1C rate are given. It can be seen that the P2 / O3 dual-phase sodium-rich layered oxide Na with five doping elements (high entropy doping) 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01 )O2 cathode material exhibits the best cycle stability and cycle capacity characteristics. After 100 cycles, the capacity has hardly decayed and remains at about 115 mAh g -1 . It is obviously superior to the P2 / O3 dual-phase sodium-rich layered oxides with three doping elements and one doping element. Fig.13 The comparison of medium rate performance shows that the high entropy doped sodium-rich P2 / O3 dual-phase layered oxide Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01 ) O2 cathode material exhibits the best rate performance. When the charge and discharge rate increases to 5C, it still remains at about 100mAhg -1 , and Na 1.33 Ni 0.26 Mn 0.67 Cu 0.07 O2、Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Fe 0.03 Cu 0.02 )O2 positive electrode materials are about 60mAhg -1 and 75mAhg -1 In particular, when the charge-discharge rate is restored to 0.5C, the high entropy doped sodium-rich P2 / O3 dual-phase layered oxide of the present invention can fully recover to a capacity of 135 mAh g at 0.5C. -1 , and Na 1.33 Ni 0.26 Mn 0.67 Cu 0.07 O2、Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Fe 0.03 Cu 0.02 )O2 positive electrode materials are only 90mAh g -1 and 100mAh g-1 , which is significantly lower than that of the high entropy doped sodium-rich P2 / O3 dual-phase layered oxide, and the capacity cannot be fully restored. The capacity can be restored, indicating that the repeated insertion and extraction of sodium ions during the high-rate charge and discharge process does not destroy the structure of the high-entropy doped sodium-rich layered oxide of the present invention, which also indicates that high entropy doping can produce a beneficial technical effect of improving the structural stability of the layered oxide material.

[0112] The high entropy doped layered oxide of the present invention exhibits excellent rate performance as a positive electrode material for sodium ion batteries, which is also related to the fact that the introduction of high entropy doping in the layered oxide can improve the conductivity of the material. The introduced multi-element produces chemical disorder and distortion, which will locally disrupt the site energy, thereby producing a distribution of site energy. When this distribution is wide enough so that the energies of adjacent sites overlap, ion hopping between them will be promoted. If this network of sites with similar energy permeates, the macroscopic ion diffusion will be enhanced due to disorder. In terms of material properties, it will show an enhancement in conductivity. This can be proved by first-principles calculations and experiments that the introduction of chemical disorder into inorganic solid electrolytes using high entropy doping can increase ionic conductivity by several orders of magnitude, thereby reducing the overall battery resistance to improve performance.

[0113] As the positive electrode material of sodium ion battery, sodium-rich P2 / O3 two-phase layered oxide with x≥1.1 is preferred to provide sufficient sodium ions to achieve the effect of sodium supplementation, more preferably, 1.1≤x≤1.5, and even more preferably, 1.1≤x≤1.34; even more preferably, a sodium-rich P2 / O3 two-phase layered oxide with high entropy doping is selected.

[0114] Example 5

[0115] Using a preparation method similar to that of Example 2 or 3, by changing the ratio of Na2CO3 and NiO, MnO2, and the oxide powder of the doping element in the raw material, the applicant also sintered and synthesized other sodium-rich P2 / O3 two-phase layered oxides, as shown in the following table:

[0116]

[0117]

[0118] It should be noted that the preparation method of high entropy doped sodium-rich P2 / O3 dual-phase layered oxide can be further adjusted. In some embodiments, in the ball milling mixing, the ball-to-material mass ratio is (5-20): 1, the dispersant is ethanol, acetone, N-methylpyrrolidone (NMP), isopropyl alcohol (IPA) or water, the ball milling speed is 300-600r / min, and the ball milling time is 3-24h; in the pressing step, the pressure is 5-30Mpa; in the sintering step, the sintering temperature is between 500-1100°C, the heating rate is 3-20°C / min, and the sintering time is 1-24h. Specific experimental conditions can be obtained by conducting a limited number of experiments based on different material types, or in other words, more optimized experimental conditions can be obtained through a limited number of experiments.

[0119] Comparative Example 1

[0120] In order to illustrate the effect of sintering temperature on the product in the high-temperature solid-phase sintering method, this comparative example provides products at different sintering temperatures, which is similar to Example 2, except that the sintering temperature is changed during the preparation process, and the phase state of the obtained product is analyzed. The results are shown in the following table:

[0121] Reaction conditions Chemical formula Phase analysis 850℃,12h <![CDATA[Na 1.33 Aunt 0.26 Mn 0.67 The 0.07 O2]]> P2 / O'3 phase 900℃,12h <![CDATA[Na 1.33 Aunt 0.26 Mn 0.67 The 0.07 O2]]> P2 phase 950℃,12h <![CDATA[Na 1.33 Aunt 0.26 Mn 0.67 The 0.07 O2]]> O3 phase

[0122] The present invention finds that the phase state of sodium-rich layered oxide is temperature-dependent. As the temperature rises, the phase state is first P2 / O'3 phase, then changes to P2 phase, then changes to P2 / O3 dual phase, and finally changes to O3 phase. That is, there is an adaptive sintering temperature range T (T1 to T2) for P2 / O3 dual phase sodium-rich layered oxide. When the sintering temperature is lower than the sintering temperature range T1, the P2 phase is formed. When the sintering temperature is higher than the sintering temperature range T2, the product gradually changes from pure P2 / O3 dual phase to O3. In the present embodiment, the sintering temperature range T is between 900°C and 950°C (900°C<T<950°C). It can be seen that the sodium-rich P2 / O3 dual phase layered oxide appears in a relatively narrow temperature range.

[0123] Comparative Example 2

[0124] Similar to Example 3, the difference is that the sintering temperature is changed during the preparation process, and the phase state of the obtained product is analyzed. The results are shown in the following table:

[0125] Reaction conditions Chemical formula Phase analysis 850℃,12h <![CDATA[Na 1.2 Ni 0.26 Mr 0.67 (Zn 0.02 No 0.02 Feb 0.01 Co 0.01 Cu 0.01 )O2]]> P2 / O'3 phase 900℃,12h <![CDATA[Na 1.2 Ni 0.26 Mr 0.67 (Zn 0.02 No 0.02 Feb 0.01 Co 0.01 Cu 0.01 )O2]]> P2 phase 950℃,12h <![CDATA[Na 1.2 Ni 0.26 Mr 0.67 (Zn 0.02 No 0.02 Feb 0.01 Co 0.01 Cu 0.01 )O2]]> O3 phase

[0126] Similar to Comparative Example 1, there is also a similar law for the phase state and temperature of the high-entropy doped sodium-rich layered oxide, that is, the high-entropy doped sodium-rich P2 / O3 dual-phase layered oxide has an adaptive sintering temperature range T (T1 to T2). In this embodiment, the sintering temperature range T is between 900°C and 950°C (900°C<T<950°C).

[0127] Comparative Example 3

[0128] Similar to Example 4, the difference is that the sintering temperature and the type of doping elements are changed during the preparation process, and the phase state of the obtained product is analyzed. The results are shown in the following table:

[0129] Reaction conditions Chemical formula Phase analysis 900℃,12h <h2 style=";text-align:left;direction:ltr"><![CDATA[Na <h2 style=";text-align:left;direction:ltr"> 1.33 <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 0.26 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.67 <h2 style=";text-align:left;direction:ltr"> (Zn<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> )O2]]><h2 style=";text-align:left;direction:ltr"> P2 / O'3 Dual Phase 930℃,12h <h2 style=";text-align:left;direction:ltr"><![CDATA[Na <h2 style=";text-align:left;direction:ltr"> 1.33 <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 0.26 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.67 <h2 style=";text-align:left;direction:ltr"> (Zn<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> )O2]]><h2 style=";text-align:left;direction:ltr"> P2 phase 950℃,12h <h2 style=";text-align:left;direction:ltr"><![CDATA[Na <h2 style=";text-align:left;direction:ltr"> 1.33 <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 0.26 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.67 <h2 style=";text-align:left;direction:ltr"> (Zn<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> )O2]]><h2 style=";text-align:left;direction:ltr"> P2 / O3 Dual Phase 1000℃,12h <h2 style=";text-align:left;direction:ltr"><![CDATA[Na <h2 style=";text-align:left;direction:ltr"> 1.33 <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 0.26 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.67 <h2 style=";text-align:left;direction:ltr"> (Zn<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> )O2]]><h2 style=";text-align:left;direction:ltr"> O3 phase

[0130] Similar to Comparative Example 1, there is also a similar rule for the phase state and temperature of the element-doped sodium-rich layered oxide, that is, the doped sodium-rich P2 / O3 dual-phase layered oxide has an adaptive sintering temperature range T (T1 to T2). In this embodiment, the sintering temperature range T is between 930°C and 1000°C (930°C<T<1000°C).

[0131] It can be seen that the sintering temperature in the high-temperature solid-phase sintering method has an influence on the phase state of the synthesized sodium-rich layered oxide. In this embodiment, the sodium-rich P2 / O3 two-phase layered oxide is preferably synthesized at a sintering temperature in the range of 900°C to 1000°C. It should be noted that those skilled in the art should know that the synthesis of a new compound is usually the result of multiple factors, and the preferred synthesis conditions for compounds of different elemental compositions may be different. In other embodiments, the sintering temperature range T of the present invention is between 800°C and 1000°C. Under the inspiration of the present invention, by adjusting factors such as elemental composition and sintering time, other sintering conditions can be obtained through a limited number of experimental optimizations, but these are all within the technical concept of the present invention.

[0132] It should be noted that in the steps of the preparation method of the present invention, the meaning of "corresponding molar ratio" in the present invention includes not only the stoichiometric molar ratio of each element in the chemical formula of the sodium-rich P2 / O3 two-phase layered oxide, but also the molar ratio of Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01 )O2 as an example. The stoichiometric molar ratio refers to the preparation of unit mole of Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01)O2, wherein the molar ratio of each element is Na:Ni:Mn:Zn:Nb:Fe:Co:Cu=1.2:0.26:0.67:0.02:0.02:0.01:0.01:0.01; that is, based on the ratio of the subscript values ​​of each element in the chemical formula; it also includes making appropriate increase or decrease adjustments to the stoichiometric molar ratio of one or more raw material components, and calculating the corresponding feed molar ratio of the actual feed amount of the raw material component; more specifically, the feed molar ratio after appropriate increase or decrease adjustment is 90% to 110% of the stoichiometric molar ratio; in specific implementations, the use of feed molar ratio and stoichiometric molar ratio both belong to the meaning of "corresponding molar ratio" of the present invention. In a specific embodiment, the actual feed molar ratio of Na2CO3 is 102% to 105% of the stoichiometric molar ratio, and the remaining Ni and Mn oxides and M oxides are calculated according to the stoichiometric molar ratio, and the feed amount is calculated according to the feed molar ratio and the stoichiometric molar ratio respectively.

[0133] It should be noted that, under the guidance of the present invention, those skilled in the art can reasonably predict that sodium-rich P2 / O3 dual-phase layered oxides with x>1 can be synthesized, and sodium-rich P2 / O3 dual-phase layered oxides Na with different values ​​of x (such as x=1.01, 1.05, 1.4, 1.5 or 2) can be obtained by changing the experimental conditions (such as pressure sintering). x A y O2 or Na x A y M z O2, these sodium-rich P2 / O3 dual-phase layered oxides with x>1 are all within the technical concept of the present invention.

[0134] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A sodium-rich P2 / O3 two-phase layered oxide, characterized in that: The chemical formula of the sodium-rich P2 / O3 dual-phase layered oxide is Na x Ni α Mn β M z O2, y = α + β , wherein Na represents sodium element, M represents a doping element, and M is selected from at least one metal element other than sodium, nickel and manganese in the third to fifth periods of the periodic table of elements, x >1,0.8≤ y< 1,0 <z ≤0.2, y + z =1; The XRD diffraction spectrum of the sodium-rich P2 / O3 dual-phase layered oxide includes: diffraction peaks of the P2 phase crystal plane (002), (004), (100), (102), (103), (104); and diffraction peaks of the O3 phase crystal plane (003), (006), (101), (102), (104).

2. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 1, characterized in that: The M is selected from the group consisting of iron, cobalt, copper, titanium, magnesium, zinc, calcium, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony and aluminum.

3. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 1, characterized in that: In the chemical formula of the sodium-rich P2 / O3 dual-phase layered oxide, 0 < α ≤0.4,0< β ≤0.7; and / or, 1< x ≤1.

5.

4. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 3, characterized in that: 0.1≤ α ≤0.4,0.1≤ β ≤0.7。 5. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 3, characterized in that: 0.2≤ α ≤0.33,0.6≤ β ≤0.7。 6. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 3, characterized in that: 0.23≤ α ≤0.33,0.67≤ β ≤0.7。 7. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 3, characterized in that: 1.1≤ x ≤1.34。 8. The sodium-rich P2 / O3 dual-phase layered oxide according to any one of claims 1 to 7, characterized in that The M is selected from five or more metal elements other than sodium, nickel and manganese in the third to fifth periods of the periodic table.

9. The sodium-rich P2 / O3 dual-phase layered oxide according to any one of claims 1 to 7, characterized in that The doping elements include at least 1 to 3 metal elements selected from the fifth period and at least 2 to 4 metal elements selected from the third period and / or the fourth period.

10. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 9, characterized in that: The metal elements of the fifth period are selected from zirconium, niobium, molybdenum, ruthenium, tin, and antimony; the metal elements of the third period are selected from magnesium and aluminum; and the metal elements of the fourth period are selected from calcium, titanium, vanadium, chromium, iron, cobalt, copper, and zinc.

11. A sodium-rich P2 / O3 dual-phase layered oxide, characterized in that: The chemical formula of the sodium-rich P2 / O3 dual-phase layered oxide is Na x (Ni α Mn β )(M 1a M 2b M 3c M 4d M 5e M 6f ) O2, y = α + β , z = a + b + c + d + e + f , M1, M2, M3, M4, M5, and M6 represent different doping elements, and the doping elements are selected from at least one metal element other than sodium, nickel, and manganese in the third to fifth periods of the periodic table of elements, x >1,0.8≤ y< 1,0 <z ≤0.2,0.1≤ α ≤0.4,0.1≤ β ≤0.7,0< a ≤0.05,0< b ≤0.05,0< c ≤0.05,0< d ≤0.05,0< e ≤0.05,0≤ f ≤0.

05.

12. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 11, characterized in that The doping element is selected from the group consisting of iron, cobalt, copper, titanium, magnesium, zinc, calcium, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony and aluminum.

13. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 11, characterized in that: 0.2≤ α ≤0.33,0.6≤ β ≤0.7; and / or, 1< x ≤1.

5.

14. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 11, characterized in that: 0.23≤ α ≤0.33,0.67≤ β ≤0.7; and / or, 1.1≤ x ≤1.

34.

15. The sodium-rich P2 / O3 dual-phase layered oxide according to any one of claims 11 to 14, characterized in that The doping elements include at least 1 to 3 metal elements selected from the fifth period and at least 2 to 4 metal elements selected from the third period and / or the fourth period.

16. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 15, characterized in that: The metal elements of the fifth period are selected from zirconium, niobium, molybdenum, ruthenium, tin, and antimony; the metal elements of the third period are selected from magnesium and aluminum; and the metal elements of the fourth period are selected from calcium, titanium, vanadium, chromium, iron, cobalt, copper, and zinc.

17. A method for preparing a sodium-rich P2 / O3 dual-phase layered oxide according to any one of claims 1 to 16, characterized in that the steps include: According to the stoichiometric molar ratio of sodium, nickel, manganese, and doping elements: x : α : β : z , weighing corresponding molar ratios of sodium salt, nickel oxide, manganese oxide and oxide doped with metal elements, and mixing them to obtain a mixed powder; Pressing the mixed powder after mixing to obtain a pressed block; The block is sintered.

18. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide according to claim 17, characterized in that: The sodium salt is selected from at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate and sodium nitrate.

19. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide as claimed in claim 17 or 18, characterized in that: The mixing process adopts ball milling; And / or, in the pressing step, the steps specifically include: loading the mixed powder into a mold and pressing and molding it; And / or, in the sintering step, the sintering temperature is between 500 and 1100° C., and the sintering time is between 1 and 24 hours.

20. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide according to claim 19, characterized in that: In the ball milling method, the ball-to-material mass ratio is (5-20):1, and the ball milling time is 3 to 24 hours; And / or, the pressurized pressure is 5 to 30 MPa; And / or, the sintering temperature is between 800 and 1000°C.

21. The method for preparing a sodium-rich P2 / O3 dual-phase layered oxide according to claim 20, characterized in that: The sintering temperature is between 900°C and 1000°C.

22. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide according to claim 20, characterized in that: The sintering temperature is between 900°C and 980°C.

23. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide according to claim 20, characterized in that: The sintering temperature is between 900°C and 950°C.

24. A method for preparing a sodium-rich P2 / O3 dual-phase layered oxide, characterized in that the steps include: According to the stoichiometric molar ratio of sodium, nickel, manganese, and doping elements: x : α : β : z , weigh the sodium salt, nickel oxide, manganese oxide and oxide of the doping element in corresponding molar ratios, and mix them to obtain a mixed powder, wherein x >1,0 <α ≤0.4,0 <β ≤0.7, α + β +z =1,0 <z ≤0.2; the sodium salt is selected from at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate and sodium nitrate; the doping element is selected from at least one of iron, cobalt, copper, titanium, magnesium, zinc, calcium, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony and aluminum; Pressing the mixed powder after mixing to obtain a pressed block; The block is sintered.

25. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide according to claim 24, characterized in that: The doping elements are selected from five or more of iron, cobalt, copper, titanium, magnesium, zinc, calcium, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony, and aluminum; And / or, the XRD diffraction pattern of the sodium-rich P2 / O3 dual-phase layered oxide includes diffraction peaks of (002), (004), (100), (102), (103), (104) crystal planes; and diffraction peaks of (003), (006), (101), (102), (104) O3 phase crystal planes; and / or, 1< x ≤1.5; and / or, 0.1≤ α ≤0.4,0.1≤ β ≤0.7; And / or, the sintering temperature of the sintering process is between 800 and 1000°C.

26. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide according to claim 25, characterized in that: 1.1≤ x ≤1.34; and / or, 0.2 ≤ α ≤0.33,0.6≤ β ≤0.7; And / or, the sintering temperature of the sintering process is between 900°C and 1000°C.

27. The method for preparing a sodium-rich P2 / O3 dual-phase layered oxide according to claim 25, characterized in that: 0.23≤ α ≤0.33,0.67≤ β ≤0.7; And / or, the sintering temperature of the sintering process is between 900°C and 980°C.

28. The method for preparing a sodium-rich P2 / O3 dual-phase layered oxide according to claim 25, characterized in that: The sintering temperature of the sintering process is between 900°C and 950°C.

29. A sodium-rich P2 / O3 dual-phase layered oxide, characterized in that: The chemical formula of the sodium-rich P2 / O3 dual-phase layered oxide is Na x A y O2, wherein Na represents the element sodium, and A is selected from the elements nickel and manganese; x >1, y =1; the XRD diffraction pattern of the sodium-rich P2 / O3 dual-phase layered oxide includes: diffraction peaks of the P2 phase crystal plane (002), (004), (100), (102), (103), (104); and, diffraction peaks of the O3 phase crystal plane (003), (006), (101), (102), (104).

30. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 29, characterized in that The chemical formula of the sodium-rich P2 / O3 dual-phase layered oxide is Na x Ni α Mn β O2, y = α + β ,0< α ≤0.4,0< β ≤0.7; and / or, 1< x ≤1.

5.

31. The sodium-rich P2 / O3 dual-phase layered oxide according to claim 30, characterized in that 0.1≤ α ≤0.4,0.1≤ β ≤0.7; and / or, 1.1≤ x ≤1.

34.

32. The sodium-rich P2 / O3 dual-phase layered oxide of claim 30, wherein: 0.2≤ α ≤0.33,0.6≤ β ≤0.7。 33. The sodium-rich P2 / O3 dual-phase layered oxide of claim 30, characterized in that 0.23≤ α ≤0.33,0.67≤ β ≤0.7。 34. A method for preparing a sodium-rich P2 / O3 dual-phase layered oxide as claimed in any one of claims 29 to 33, characterized in that the steps include: According to the stoichiometric ratio of sodium, nickel and manganese elements: x : α : β , weighing sodium salt, nickel oxide and manganese oxide in corresponding molar ratios, and mixing them to obtain a mixed powder; Pressing the mixed powder after mixing to obtain a pressed block; The block is sintered.

35. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide according to claim 34, characterized in that: The sodium salt is selected from at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate and sodium nitrate; And / or, the sintering temperature of the sintering process is between 800°C and 1000°C.

36. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide according to claim 35, characterized in that: The sintering temperature of the sintering process is between 900°C and 1000°C.

37. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide according to claim 35, characterized in that: The sintering temperature of the sintering process is between 900°C and 980°C.

38. The method for preparing the sodium-rich P2 / O3 dual-phase layered oxide according to claim 35, characterized in that: The sintering temperature of the sintering process is between 900°C and 950°C.

39. A sodium ion battery positive electrode material, characterized in that: It comprises the sodium-rich P2 / O3 dual-phase layered oxide as described in any one of claims 1 to 16 and 29 to 33; or the sodium-rich P2 / O3 dual-phase layered oxide obtained by the preparation method as described in any one of claims 17 to 28 and 34 to 38.

40. A sodium ion battery, characterized in that: Comprising the sodium ion battery positive electrode material as described in claim 39.

41. An electrical device, characterized in that: Comprising a sodium ion battery as claimed in claim 40.

Citation Information

Cited By

  • P2 / O3 two-phase layered oxide as well as preparation method and application thereof

    CN119797438A